Clinical, microscopic and molecular presentation in pediatric versus adult old world cutaneous Leishmaniasis. Issue 4 (18th May 2020) - Dunya, Gabriel; Loya, Asif; Taraif, Suad; Adib Houreih, Mohammad; Khalifeh, Ibrahim
Abstract: Background: Cutaneous leishmaniasis (CL) is an emerging uncontrolled tropical parasitic disease in endemic and nonendemic areas with a high prevalence in the pediatric age group. Method: A total of 382 individuals from Lebanon, Saudi Arabia, Pakistan, and Syria diagnosed with CL by punch biopsy/scrapings were grouped into adults (>18 years) and pediatrics (≤18 years). Data recorded included clinical features [number, location, type, size, and extensiveness (size larger than 3 cm, more than 5 lesions per patient, lesion present for more than 12 months, special types, disfiguring lesion or closeness to vital sensory organs) of lesions] and microscopic findings [Ridley's Parasitic Index and Ridley's Pattern]. In addition, molecular confirmation and speciation were performed. Results: In comparison with adults, patients in the pediatric group (n = 158, 41.4%) showed significantly higher number of lesions, more facial involvement, and more extensive disease ( P  < .05). Microscopically, a more advanced Ridley's pattern was observed. The other variables did not show statistical difference between the two groups. Conclusion: Historically, CL has been known to be a neglected tropical disease of poverty and pediatric predilection. In our pediatric group, CL manifests with more extensive disease clinically mirrored by more advanced lesions microscopically.